The Ups and Downs of Cocoa Prices on Farmers' Welfare: A Sustainability Accounting Perspective - Nurriskiana Akbar; Sugianto; Muhammad Ikbal Abdullah; Ernawaty Usman (GoodWill Journal of Economics, Management, and Accounting, 2025)
This research aims to understand the factors that influence the ups and downs of cocoa prices, their impact on farmers' welfare, and explore the role of sustainability accounting in strengthening the economic resilience of cocoa farmers. Using a descriptive qualitative approach, this study explores the experiences and adaptive strategies developed in dealing with price dynamics and maintaining sustainable plantation practices. The findings show that cocoa price volatility is influenced by imbalances between demand and supply, climate change, and global market volatility. These price fluctuations have an impact on the socio-economic conditions of farmers: when prices rise, farmers' incomes increase which allows the fulfillment of basic needs and sustainability investments; On the contrary, falling prices create economic pressures and a decrease in quality of life. The implementation of sustainability accounting has been proven to help farmers manage risks, as well as maintain sustainable plantation business practices amid market uncertainty. These findings are expected to contribute to the formulation of policies that are in favor of improving the welfare of cocoa farmers and strengthening sustainable plantation development.